Brief Exercise at Work (BE@Work): A Mixed-Methods Pilot Trial of a Workplace High-Intensity Interval Training Intervention - Burn, Naomi L.; Weston, Matthew; Atkinson, Greg; Graham, Michael; Weston, Kathryn L. (Frontiers in Sports and Active Living, 2021)
Introduction: The efficacy of high-intensity interval training (HIIT) for improving markers of physical fitness and cardiometabolic health is promising. The workplace is one non-laboratory setting where the effectiveness of HIIT could be explored. The aim of this study was to undertake a mixed-methods exploratory pilot trial of a workplace HIIT intervention named Brief Exercise at Work (BE@Work). Methods: Fifty-four healthy employees (mean ± standard deviation [SD] age 46 ± 10 years) from two workplaces in Northeast England were allocated to 8 weeks of thrice-weekly workplace HIIT based on boxing, stair climbing and stepping, comprising 4–7 60 s high-intensity intervals interspersed with 75 s rest (n = 30), or a no-intervention control (n = 24). The primary outcome was the change SD of predicted maximal oxygen consumption (VO2max). Markers of physical fitness, cardiometabolic health and mental well-being were also measured at baseline and follow-up. Participant perceptions of the intervention were explored in post-intervention focus groups (n = 9). Results: Mean (±SD) session attendance was 82% (±15%). Mean peak heart rate across the intervention was 87% of age-predicted maximal heart rate with a within- and between-subject SD of 5.5% and 3.7%, respectively. The SD of changes in predicted VO2max was 6.6 mL·kg−1·min−1 across both groups, which can be used to inform sample size estimations for a future full trial. The control-adjusted mean increase (95% confidence interval) in predicted VO2max was 3.9 (−0.2 to 8.1) mL·kg−1·min−1, corresponding to a Cohen's D of 0.47. We also observed preliminary evidence of small to moderate effects in favour of the intervention group for non-dominant leg extensor muscle power, markers of health-related quality of life, well-being and perceived stress and small to moderate effects in favour of the controls in perceived pain, physical activity and high-density lipoprotein cholesterol. During HIIT, focus group participants reported physiological responses they perceived as unpleasant or tiring (e.g., breathlessness, local muscular fatigue), but also that they felt alert and energised afterwards. Conclusion: The findings of this exploratory pilot trial support the implementation of a definitive randomised controlled trial to quantify the effectiveness of a workplace HIIT intervention.